Food frequency questionnaire for dietary intake of iron in pregnancy- A validation study - B.M. Bhagyashri; Sheetal Harakuni; Yeshita Pujar; Jang Bahadur Prasad (Clinical Epidemiology and Global Health)
Background and objective: Nutrition in pregnancy plays an important role for wellbeing of mother and fetus, later it further influences the development of child. Iron is one among the most important micronutrients required in pregnancy. There is no validated Food frequency questionnaire (FFQ) to assess iron intake in pregnant women. This initiated the process to develop and validate a FFQ to assess dietary intake of Iron in Pregnant women. Methodology: Based on the food habits in study region and foods rich in iron, in reference to the standard literature, the FFQ was prepared. FFQ was designed in the following categories-cereal grains and products, pulses & legumes, green leafy vegetables, roots-tuber & other vegetables, nuts & seeds, Fruits, non-veg foods and milk & milk products. Content validity carried out by subject experts. To perform construct validity, 25 Primary health centre and 25 Tertiary care hospital pregnant women were interviewed using this FFQ and 24 h diet recall method. The results of both records were analyzed using Wilcoxon signed rank test. Internal reliability (Cronbach's alpha) and construct validity (Pearson correlation) of the questionnaire were determined. Results: Overall internal reliability of questionnaire is 0.804, indicating good reliability and showing satisfactory construct validity. Median dietary iron intake from FFQ method was 7.67 mg/day and 24 h dietary recall method was 15.70 mg/day. There was a significant difference between both method in assessing dietary iron intake. Conclusion: The FFQ designed in this study is reliable and valid tool to assess dietary iron intake among pregnant women.